From Agricultural to Landless: Studi Dampak Pembangunan Bantul Kota Mandiri - Endang Purwasari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
The land crisis that occurred in Yogyakarta is increasing every year. An area that is experiencing an increasing agricultural land crisis is the Bantul Regency. The Bantul Regency Government supports land conversion by issuing local regulations concerning the development of Bantul Kota Mandiri (BKM). As stated in the regional regulation, the western part of Bantul is designated for elite housing, recreation, trade, education, and others. More than 100 hectares of community land were prepared for the realization of the program. This ethnographic study takes place in the Merindu Village part of the BKM Area. It involved six females and three males as main informants and several people who take part in incidental interviews. Data were collected using in-depth interviews to cultivate the impact society faces and strategies in managing land compensation. While participatory observation is carried out by participating in the daily activities of the Merindu village community, such as arisan, attending parties, social gatherings, etc. This research also uses data from the media to give a perspective of the government plan. BKM establishment not only affects the reduction of agricultural land but there will be a job change, an increasing flow of population, and will cause social and culture shock for the local people. The social impact has already happened. Compensation money received by residents, especially the young generation, is used for consumptive property not for productive property. They choose to become laborers in the industrial sector rather than work on their farmland. From this point, Bantul will face a consumptive young generation and a land crisis.